Synthesis, antioxidant and anti-inflammatory properties of an apocynin-derived dihydrocoumarin - Paracatu, Luana C. [UNESP]; Zeraik, Maria L.; De Carvalho Bertozo, Luiza [UNESP]; De Andrade Bartolomeu, Aloisio [UNESP]; Da Silva Filho, Luiz C. [UNESP]; Da Fonseca, Luiz M. [UNESP]; Ximenes, Valdecir F. [UNESP] (Bentham Science Publishers, 2017)
Background: Coumarin derivatives as dihydrocoumarins have been reported to have multiple biological activities, such as antioxidant and anti-inflammatory properties. Apocynin (APO), which is a substituted-methoxy-catechol, is the most commonly used inhibitor of the multienzymatic complex NADPH-oxidase. Objective: To increase the potency of APO as an NADPH oxidase inhibitor and its antioxidant and anti-inflammatory activities, we synthesized a compound by combining the structural features of a dihydrocoumarin and APO. Method: The dihydrocoumarin-apocynin derivative (HCA) was synthesized and evaluated in antioxidant and cell-based bioassays and compared with APO. Results: We found that HCA (IC50 = 10 μM) acted as an inhibitor of NADPH oxidase (ex vivo assays) and was more potent than APO (EC50 > 10 μM). The inhibitory effect on NADPH oxidase was not related to simple radical scavenger activity. HCA was also a more effective radical scavenger than APO, as verified in the DPPH (EC50 = 50.3 versus EC50 > 100 μM), triene degradation (slope AUC/concentration 759 ± 100 versus 101 ± 15) and FRAP (slope 0.159 versus 0.015) assays. The tested compound demonstrated a similar activity as an inhibitor of the oxidative damage provoked by peroxyl radicals in erythrocyte membranes. Conclusion: HCA showed superior capacity as inhibitor of NADPH oxidase and antioxidant activity. These findings show that HCA could be an improved substitute for APO and deserves further in vivo anti-inflammatory studies.
Keywords: Antioxidant; Apocynin; Coumarin; NADPH oxidase; Neutrophils